Keith R. Legg - John Μ. Roberts, Modern Greece: A Civilization on the Periphery, Boulder, Colorado, Westview Press, 1997,235 σελ. - Τσακρακλίδου, Σοφία Π. (Ελληνική Επιθεώρηση Πολιτικής Επιστήμης, 2017)
Δεν διατίθεται περίληψη.